Estimasi Potensi Cadangan Air Tanah Dengan Metode Persamaan Darcy di Desa Pilomonu, Gorontalo - Sugianti, Komang; Zainuri, Ahmad; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2022)
This research aims to know the prediction of potential for groundwater reserves. The research method applies surface geological mapping and subsurface data collection with the 200-span Schlumberger configuration geoelectric method. The stratigraphy of the research area is sorted from old to young, the first is the granodiorite unit, the sandstone unit, and alluvial units are deposited inconsistently. The geological structure working in the research area has a dominant northwest-southeast direction. The direction of. groundwater flow follows the topography of the research area, whicb is flowing from the north to the south, where the elevation of the norlh js higher than the eJevation of the south. The aquifer characteristics in the research area can be divided into two based on the mterpretation of geoelectric inversion, such as shallow aquifer with material in the form of sand and deep aquifer with sand and gravel material. Prediction of the potential for groundwater reserves is obtained from the interpretation of geoelectric data and data from the calculation of the groundwater level in the research area by observing the. conditions around the research area So, it is obtained a prediction of potential for shallow groundwater reserves is 360.444 m3/day or equivalent to 360,444 liters/day, and the prediction of poteptial deep groundwater reserves is 66,520.476 m3/day or equivalent to 66:,520,476 liters/day.